Efektivitas Program Pembinaan Industri Rumah Tangga Sari Buah di Kota Depok - Puspa Mega Hayati; Winiati Pudji Rahayu; Siti Nurjanah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
The main factor that causes food safety problem in home industries is lack of good manu-facturing practices (GMP) implementation. The objective of this research were to evaluate the imple-mentation of GMP, identify coliform and Escherichia coli contamination in fruit juices, evaluate effec-tiveness of fostering assisted program based on implementation of GMP criteria, and compose the recommendation of fostering assisted program for fruit juice home industries in Depok. The fostering assisted program have been given for certain periode to lower level home industries showed the decrease of unconformities factors for industries D, E, F and increase of industries level. The effectiveness scores of fostering assisted program provided for industry D and E were 1, and F was 0.83; indicated the good achievement. There were not found coliform and Escherichia coli in juice samples from industries D, E, and F (starfruit juice samples), whereas there found coliform in guava juice samples from industry F (5.2 x 102 APM/mL) and the result of Escherichia coli test was negative before fostering assisted program. After fostering assisted program, the result of coliform test to guava juice samples of F was negative.